MODELS OF ORGANIC CERTIFICATION IN HERBAL SECTOR OF TRANSITIONAL COUNTRIES OF WESTERN BALKAN (SE EUROPE) - Redzic, S.; Basic, H.; Barudanovic, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Intensive processes of transition in countries of Western Balkan, as well as transition from central economy to market economy have left visible marks on natural resources. Organic certification is aimed toward safety, sustainability and better administration of plants. Evaluation and identification of safety includes the following: application to company in charge for organic certification; visiting places of future exploitation; mapping of territory for gathering medicinal plants and ensuring ecological certificate, issued by ministry in charge, that would guaranty safety of the territory in terms of pollution, use of pesticides, artificial fertilizers, global influences. In administration, it is necessary to conduct permanent education of harvesters and other people employed in herbal sector, to conduct accreditation of people, development of more solid legislation and more effective monitoring and inspections. In order to reach sustainability in use of natural resources, it is necessary to have on disposal the following: list of wild medicinal plants, their biomass, models of reproduction, affiliation with living forms, conservation status, etc. Higher level of sustainability, as well as improvement of overall methodology of organic certification in herbal sector includes evaluation of conditions and bearing capacities of ecosystems on exploitive territory, evaluation of sustainable biomass of plants, evaluation of level of biological and ecological sensitivity of medical plants, establishment of herbal management plant, strengthening human resources and state institutions. Study is demonstrating samples from various bio-geographical areas of western Balkan from Mediterranean to high mountains of Bosnia and Herzegovina.